Conservation Triage Falls Short Because Conservation Is Not Like Emergency Medicine - Vucetich, John A.; Nelson, Michael Paul; Bruskotter, Jeremy T. (Frontiers in Ecology and Evolution, 2017)
Conservation triage, as a concept, seems to have been born from analogizing circumstances that characterize conservation with triage, as the concept applies to emergency medicine. Careful consideration—facilitated through the aid of formal argumentation—demonstrates the critical limitations of the analogy. Those limitations reveal how the concept of conservation triage falls short. For example, medical triage presupposes that resources available for an emergency are limited and fixed. By contrast, the resources available for conservation are not fixed. Moreover, the ethics of prioritization in medical triage is characterized by there being universal agreement on the moral value of the patients. However, in conservation there is not universal agreement on the value of various objects of conservation concern. The looming importance of those features of conservation—disputed values and unfixed resources—make conservation triage a largely un-useful concept.